Correlation analysis of cytokine levels and Th2, Th17, and Treg cells in allergic rhinitis: Cytokine levels in allergic rhinitis - Yao, Mei; Liu, Luoguo; Wen, Jingda; Zhang, Weishi (Journal of Medical Biochemistry, 2025)
Objective: To explore the roles of Th2, Th17, and regulatory T (Treg) cells and their related cytokines and transcriptional genes in the pathogenesis of allergic rhinitis (AR).Methods: A total of 200 patients who were diagnosed with AR in our hospital from October 2023 to October 2024 were randomly selected as the AR group. According to the visual analog scale (VAS) score, the AR group was further divided into a mild allergic rhinitis group (MAR group) and a severe allergic rhinitis group (SAR group). Moreover, 50 healthy people who underwent physical examinations at the Physical Examination Center of Ordos Central Hospital composed the healthy control group (HC group). Blood from peripheral veins was drawn on the day of registration. The Th17/Treg ratio and the proportions of helper T 2 (Th2), helper T 17 (Th17), and Using flow cytometry, the number of regulatory T (Treg) cells among the peripheral blood's CD4+T cells was determined. The enzyme-linked immunosorbent assay (ELISA) was used to determine the levels of interleukin-4 (IL-4), interleukin-5 (IL-5), interleukin-10 (IL-10), and interleukin-17 (IL-17) in the patients' serum. The genes GATA-3 mRNA, RORyt-mRNA, and FOXP3-mRNA's relative expression levels were assessed using real-time fluorescence quantitative RT-PCR of peripheral blood mononuclear cells.Results: The peripheral blood of AR patients had larger Th2/Th17/Treg cell proportions and a higher Th17/Treg ratio. The AR group presented greater differences (P
Keywords: Allergic rhinitis; Cytokine level; Th2 cell; Th17 cell; Treg cell; Correlation analysis